Effectiveness of public innovation support in Europe: Does public support foster turnover, employment and labour productivity? - Lasse Becker (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
In the European Union (EU), twenty Member States offer public innovation support for private research and development (R&D) activities through either subsidies or a combination of tax cuts and subsidies. Existing studies show ambiguous results regarding the effectiveness of public innovation support in different countries. Accordingly, following a description of the current public innovation framework in Europe, this paper analyses data from the European Community Innovation Survey concerning the effectiveness of public support. The measures chosen relate to changes in turnover as well as the number of employees and labour productivity (measured as turnover per employee) between 2006 and 2008. The paper finds a positive influence of public innovation support on labour productivity in an innovating company, a negative influence on turnover changes and a negative yet not significant influence on the development of employment. The influences of these factors are very weak, whereas other coefficients such as the money spent on innovative activities clearly show positive effects for all three indicators.
Keywords: O31; O38; H21; 330; innovation; innovation support; labor productivity; Europe; effectiveness